Feeding Patterns of Children Under 24 Months with Severe Acute Malnutrition at Khyber Teaching Hospital, Peshawar - Ali, Wajid; Khaliq, Abdul; Aziz ur Rahman; Akbar, Sadiq; Shah, Maarij Ullah; Ibadullah (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the feeding patterns among children under 24 months presenting with severe acute malnutrition. Study design: Cross-sectional Study. Place and duration of study: Department of Pediatrics, MTI, Khyber Teaching Hospital Peshawar, from 11th of August 2024 to 11th February 2025. Methodology: A total of 325 children under 24 months of age diagnosed with severe acute malnutrition (as defined by WHO criteria) were included in this study through consecutive sampling. All the data regarding sociodemographic characteristics, feeding patterns and nutritional practices were collected through structured interviews with mothers, clinical examinations, and anthropometric measurements. Descriptive analysis was done to determine the feeding patterns among these children presenting with severe acute malnutrition. Results: The mean age of children in this study was 13.14±5.96 months. Males constituted 52% of the total study population, while females accounted for 48%. The demographics and socioeconomic characteristics showed that most of the children belonged to age group of 7-12 months (31.4%), most were rural residents (51.7%), most of the mothers had primary level of education (39%) and majority were belonging to lower income status (53%). The details of feeding patterns showed that most of the children were never breastfed/had early cessation of breastfeeding (56.3%). A notable proportion had started earlier mixed feeding (40.3%), started complementary feeding after 6 months (41%) and were having ˂3 meals/day (35%). Conclusion: Suboptimal feeding practices in shape of early cessation of breastfeeding, inappropriate mixed feeding and lack of complementary feeding significantly contribute to severe acute malnutrition in children under 24 months.